PENGARUH SISTEM INFORMASI MANAJAMEN TERHADAP PENINGKATAN KUALITAS PELAYANAN DI PT. JASARAHARJA PUTRA CABANG BENGKULU - Ilham Agustian; Harius Eko Saputra; Antonio Imanda (Professional: Jurnal Komunikasi dan Administrasi Publik, 2019)
his study aims to find the influence of variable X (Management Information System) on variable Y improvement (Service Quality) study at PT. Jasaraharja Putera Bengkulu Branch. This study used a quantitative method with data analysis techniques of Product Moment Correlation analysis. Data collection was done using library techniques, observation, questionnaires (questionnaires), and documentation. The number of samples in this study was 55 respondents. The results of this study indicate that the level of correlation between independent variables (X) the influence of management information systems on variables (Y) improving service quality is in the low category because it is located between 0.20 - 0.399. This proves that the variable X (management information system) with variable Y (service quality) can be declared influential but included in the low category. Management information system (X) has a significant effect on service quality (Y). This can be seen from the results of the t-test calculation of 2,783. While the results of the calculation of determination r2 = 0.128 or equal to 12.8% which contains the understanding that the influence of independent variables (management information systems) on the dependent variable increase (service quality) is 12.8% and can be declared weak, while the remaining 87.2% is caused by other factors not examined by the researcher.